2018
DOI: 10.3390/ijms19082215
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neohesperidin Dihydrochalcone Analogue Inhibits Adipogenic Differentiation of Human Adipose-Derived Stem Cells through the Nrf2 Pathway

Abstract: Obesity, characterized by excess lipid accumulation, has emerged as a leading public health problem. Excessive, adipocyte-induced lipid accumulation raises the risk of metabolic disorders. Adipose-derived stem cells (ASCs) are mesenchymal stem cells (MSCs) that can be obtained from abundant adipose tissue. High fat mass could be caused by an increase in the size (hypertrophy) and number (hyperplasia) of adipocytes. Reactive oxygen species (ROS) are involved in the adipogenic differentiation of human adipose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…The representative compound of qingpi, neohesperidin, a flavonoid glycoside with a strong bitter taste [ 54 ], is also one of the most important natural flavonoid glycosides, with strong anti-inflammatory, anticancer, and cardiovascular protective effects [ 55 ]. Relevant research results show that neohesperidin can significantly inhibit the proliferation of breast cancer (MCF-7 cells) in a dose-dependent manner [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The representative compound of qingpi, neohesperidin, a flavonoid glycoside with a strong bitter taste [ 54 ], is also one of the most important natural flavonoid glycosides, with strong anti-inflammatory, anticancer, and cardiovascular protective effects [ 55 ]. Relevant research results show that neohesperidin can significantly inhibit the proliferation of breast cancer (MCF-7 cells) in a dose-dependent manner [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neohesperidin, another well-known compound of the Citrus genus, also has an AMPK-dependent lipid-regulating effect in vivo and vitro [63]. Further studies reported the anti-adipogenic or anti-obese effect of naringin [64,65,66,67] and neohesperidin [68,69], nevertheless, none of these have established the effect of either compound on UCP1-mediated thermogenesis. Our LC-MS data suggests that these two constituents may be responsible for the AMPKα-dependent anti-adipogenic and thermogenic effect of CA, however, to clarify, further investigation should be carried out with different fractions and/or identified constituents.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrobium officinale polysaccharides (DOPs) significantly promoted osteoblast differentiation and inhibited adipogenic differentiation of BMSCs by activating NRF2 pathway ( 78 ). The novel neohesperidin dihydrochalcone analogue inhibits adipogenic differentiation of human adipose-derived stem cells via the NRF2 pathway as well ( 79 ). Panax ginseng fruit protects against porphyromonas gingivalis lipopolysaccharide (PG-LPS)-induced osteoblastic differentiation injury in hPDLCs by activating the NRF2/HO-1 signaling pathway ( 80 ).…”
Section: Nrf2 and Bone Cellsmentioning
confidence: 99%